The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1556/034.57.2015.3-4.11
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the growth of young individuals of Pinus nigra on thin carbonate soils under climate change in Hungary

Abstract: Climate change highly impacts on tree growth and also threatens the forest of the karstic terrains. From the 1980s the frequency of decay events of the Pinus nigra Arnold forests showed a marked increase in Hungary. To understanding the vulnerability of Pinus nigra forests to climate change on shallow karstic soils in continental-sub Mediterranean climatic conditions we developed the study of three sampled population in the typical karstic landscape of Veszprém in North Transdanubia. We built our model on non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Model results showed that the rising decay frequency of Pinus nigra individuals in the last decades was a parallel change to the decreasing growth rate of pines due to the increasing aridity trend in the Veszprém karst plateau (Trájer et al 2015). As drought inhibits growth (Chiatante et al, 2006;Kramer and Turner 1980), in this paper, we investigate the effect of the sub-regional drought trends and the foreseen change of precipitation and temperature on the stem growth of young individuals of Fraxinus ornus and its two most important competitors: Pinus nigra and Ailanthus altissima.…”
Section: Introductionmentioning
confidence: 99%
“…Model results showed that the rising decay frequency of Pinus nigra individuals in the last decades was a parallel change to the decreasing growth rate of pines due to the increasing aridity trend in the Veszprém karst plateau (Trájer et al 2015). As drought inhibits growth (Chiatante et al, 2006;Kramer and Turner 1980), in this paper, we investigate the effect of the sub-regional drought trends and the foreseen change of precipitation and temperature on the stem growth of young individuals of Fraxinus ornus and its two most important competitors: Pinus nigra and Ailanthus altissima.…”
Section: Introductionmentioning
confidence: 99%